2021
DOI: 10.1186/s12879-021-06075-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of prosthetic joint infections in France: a national audit to identify key situations requiring innovation and homogenization

Abstract: Background Prosthetic joint infections (PJI) are one of the most serious complication of arthroplasty. The management of PJI needs a multidisciplinary collaboration between orthopaedic surgeon, infectious disease specialist and microbiologist. In France, the management of PJI is organized around reference centres (CRIOACs). Our main objective was to perform an audit through a questionnaire survey based on clinical cases, to evaluate how French physicians manage PJI. Eligible participants were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…More generally, in their experience, clindamycin-combination therapy appeared to be effective against erythromycin-resistant, lincosamide-susceptible staphylococcal BJIs [69]. According to a 2019 French national audit on the management of PJIs, clindamycin was a frequent choice, when fluoroquinolones or rifampicin were not available [70]. Other oral rifampicin combination partners include co-trimoxazole, minocycline or doxycycline [5] and linezolid.…”
Section: Staphylococcal Pjismentioning
confidence: 99%
See 3 more Smart Citations
“…More generally, in their experience, clindamycin-combination therapy appeared to be effective against erythromycin-resistant, lincosamide-susceptible staphylococcal BJIs [69]. According to a 2019 French national audit on the management of PJIs, clindamycin was a frequent choice, when fluoroquinolones or rifampicin were not available [70]. Other oral rifampicin combination partners include co-trimoxazole, minocycline or doxycycline [5] and linezolid.…”
Section: Staphylococcal Pjismentioning
confidence: 99%
“…Despite its high bioavailability and in vitro efficacy against methicillin-resistant staphylococci [78], linezolid was the last choice to treat staphylococcal PJIs in a French national audit, probably because of its safety profile and the restricting nonuse beyond 4 weeks [71,[78][79][80][81][82]. Study results showed increased tolerability of prolonged tedizolid administration [70,83], but data for broader use are lacking [84].…”
Section: Staphylococcal Pjismentioning
confidence: 99%
See 2 more Smart Citations